2015
DOI: 10.1002/aic.15034
|View full text |Cite
|
Sign up to set email alerts
|

Use of CuO/MgAl2O4 and La0.8Sr0.2FeO3/γ‐Al2O3 in chemical looping reforming system for tar removal from gasification gas

Abstract: in Wiley Online Library (wileyonlinelibrary.com)Biomass gasification gas contains condensable hydrocarbons usually referred to as "tars." The use of chemical-looping reforming (CLR) has been proposed as a downstream technology for tar removal. The tar removal capabilities and the regeneration properties of two particularly promising bed materials, CuO/MgAl 2 O 4 and La 0.8 Sr 0.2 FeO 3 /c-Al 2 O 3 , were investigated using C 2 H 4 , C 6 H 6 , and C 7 H 8 as tar surrogates. The material La 0.8 Sr 0.2 FeO 3 /c-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Also, the mechanical strength and antisintering of the oxygen carrier need to be concerned . Up to now, metallic oxides including Cu, Fe, Co, Ni, and Mn as well as nonmetallic oxides such as CaSO 4 , have been widely studied as oxygen and heat carriers in chemical looping combustion (CLC) or CLG process. Among them, Ni-based oxygen carriers have attracted much attention due to their higher redox activity and catalytic effect to decompose tar.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the mechanical strength and antisintering of the oxygen carrier need to be concerned . Up to now, metallic oxides including Cu, Fe, Co, Ni, and Mn as well as nonmetallic oxides such as CaSO 4 , have been widely studied as oxygen and heat carriers in chemical looping combustion (CLC) or CLG process. Among them, Ni-based oxygen carriers have attracted much attention due to their higher redox activity and catalytic effect to decompose tar.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that B-site dopant will have a higher impact than the A-site dopant on vacancy creation, which is related to the oxygen release ability of the compound . However, the effect of MgO addition to the B site was tested for a CLOU application. , A study revealed that MgO-doped CaMnO 3 showed good stability in a 50-cycle test and a small increase in reactivity was also observed . Both in thermal analysis and fluidized bed experiments (Figures and for CMM1 and CMM2, respectively), the reduction peak temperature was observed around 975–985 °C for both MgO-doped CaMnO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Both supports and promoters have been tested to alleviate the sintering problem. The addition of inert supports such as Al 2 O 3 [133,[296][297][298], TiO 2 [133,297,299], and MgAl 2 O 4 [300] can slow down the sintering problem of copper oxide, but the addition of Al 2 O 3 , an acidic support, leads to the aggravation of carbon deposition [301]. As a result, Alirezaei et al [193] incorporated ZrO 2 into Al 2 O 3 , which promoted the dispersion of copper oxide and adjusted the mechanical properties of oxygen carriers.…”
Section: Copper Based Oxygen Carriermentioning
confidence: 99%